Micropolíticas da criação : os processos compartilhados da Confraria dos Atores (MT) e do Teatro do Concreto (DF) - Moura, Jandeivid Lourenço (2012)
Reflections on the means of construction of a theater that broke with traditional processes of creation, taking as reference the ‘80s and '90s theater with its experimental laboratories. For this work, two theater companies from the Central-West region of Brazil, the Teatro Concreto and the Confraria dos Atores, were observed on its processes of shared creation. Michel Foucault and the power issue bring elements to problematize the traditional means and Gilles Deleuze and Felix Guattari support the matter of the micropolitics, named here as micropolitics of creation, for the analysis of the experiments in collaborative processes from the theater companies observed.